Finding Email in a Multi-Account, Multi-Device World - Cecchinato, Marta E.; Sellen, Abigail; Shokouhi, Milad; Smyth, Gavin (2016 Human Factors in Computing Systems, 2016)
Email is far from dead; in fact the volume of messages exchanged daily, the number of accounts per user, and the number of devices on which email is accessed have been constantly growing. Most previous studies on email have focused on management and retrieval behaviour within a single account and on a single device. In this paper, we examine how people find email in today's ecosystem through an in-depth qualitative diary study with 16 participants. We found that personal and work accounts are managed differently, resulting in diverse retrieval strategies: while work accounts are more structured and thus email is retrieved through folders, personal accounts have fewer folders and users rely primarily on the built-in search option. Moreover, retrieval occurs primarily on laptops and PCs compared to smartphones. We explore the reasons, and uncover barriers and workarounds related to managing multiple accounts and devices. Finally, we consider new design possibilities for email clients to better support how email is used today.